مضار الجوار غير المألوفة - خيري، مرتضى عبدالله (قارة وليد, 2016)
اختلف الفقهاء في تحديد الأساس الذي تقوم عليه المسؤولية عن مضار الجوار غير مألوفة الي عدد من الآراء فمنهم من أسسها على الخطا الشخصي بتجاوز التزام قانوني مبعثه الجوار ومنهم من أسسها على التعسف وآخرون قالوا بانها من قبيل مسؤولية حارس الأشياء كما أسسها البعض على فكرة تحمل التبعة والواقع أنها ترجع الي قيود الملكية الخاصة بعلاقات الجوار فهي مسؤولية يمليها التضامن الاجتماعي بين الجيران وسوف نتناول موضوع الاضرار غير المألوفة في قانون المعاملات المدنية العماني والذي اعتبر الأضرار بالغير ضررا غير مألوف مجرد تطبيق من تطبيقات الاستعمال غير مشروع للحق.
Scholars differed in determining the basis of the responsibility about the harms of the unfamiliar neighborhood to a number of opinions. Some of them based on the personal fault bypass a legal commitment neighborly motivated, and some of them based on arbitrariness, and others said that it is the liability of guard of things as some based on the idea of carrying consequencies. Indeed, it is due to private ownership restrictions by neighborly relations, so, it is a responsibility dictated by social solidarity between neighbors, and we will address the subject of harms of the unfamiliar neighborhood in the Omani civil transactions Act, which considered harms to others as a unfamiliar harm, it is just an application from illegally use applications to the right
Keywords: القوانين والتشريعات -- القانون المدني -- الملكية -- حقوق الجار -- القانون المقارن